2013
DOI: 10.1890/13-0396.1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of predators and trematode parasites on larval green frog (Rana clamitans) survival

Abstract: Parasites and predators can have complex, nonadditive effects on a shared group of victims, which can have important consequences for population dynamics. In particular, parasites can alter host traits that influence predation risk, and predators can have nonconsumptive effects on prey traits which influence susceptibility (i.e., infection intensity and tolerance) to parasites. Here, we examined the combined effects of trematode parasites (Digenea: Echinostomatidae) and odonate (Anax) predators on the survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 64 publications
5
34
1
Order By: Relevance
“…Furthermore, we did not observe a negative effect of parasitism on survival that we had previously observed (Marino & Werner, 2013). Furthermore, we did not observe a negative effect of parasitism on survival that we had previously observed (Marino & Werner, 2013).…”
Section: Comparison With Previous Experimentscontrasting
confidence: 49%
See 3 more Smart Citations
“…Furthermore, we did not observe a negative effect of parasitism on survival that we had previously observed (Marino & Werner, 2013). Furthermore, we did not observe a negative effect of parasitism on survival that we had previously observed (Marino & Werner, 2013).…”
Section: Comparison With Previous Experimentscontrasting
confidence: 49%
“…Nevertheless, other recent studies have similarly reported no effect (Raffel et al, 2010;Marino & Werner, 2013) or even a positive effect (Johnson et al, 2013;Wojdak et al, 2014) of density on larval amphibian trematode infection at the mesocosm scale. Our sample sizes for dissection were limited and necessarily did not include animals that died during the experiments, as dead tadpoles are typically not visible in the large mesocosms and rapidly degrade.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…1). Green frog tadpoles, Lithobates clamitans, exposed to free-living stages of trematode parasites increased their activity levels as an avoidance response (Marino & Werner, 2013). As a result, tadpoles experienced greater predation rates by larval dragonflies, which target highly active prey.…”
Section: Communitiesmentioning
confidence: 99%